A mistura dos bósons Z − Z′ e a quebra explícita da simetria leptônica no modelo 331 com neutrinos de m ao direita - Diniz Filho, Hermes Mangueira (2009)
In this thesis, we develop some phenomenological aspects of a model based on the gauge symmetry SU(3)CNSU(3)LNU(1)N (311νR), that include righthanded neurinos in its matter content. We establish all the necessary structure for the study of the phenomenological aspects of the model. First, we obtain bounds on the angle that mix the gauge bosons Z and Z′, taking into account a requirement of the model, namely, that the number of fermionic families is exactly three. Also we implement the mass for both species of neutrinos (left-hand and right-handed) via type II seesaw mechanism, obtained adding to the model a sextet of scalars which will be responsible by the violation of the lepton number. The main consequence is the rising of a sterile neutrino with mass in the KeV range, satisfying all the cosmological and astrophysical constraints. This neutrino will a viable candidate for warm dark matter in the universe.